2020
DOI: 10.4067/s0717-97072020000404943
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Oxytetracycline by Polymers. An Overview

Abstract: Oxytetracycline (OTC) is an antibiotic belonging to the tetracycline family, widely used in veterinary medicine due to its pharmacological characteristics and adequate cost/effectiveness ratio. One of the problems presented by the therapeutic use of antibiotics such as OTC is that they do not metabolize and are expelled through animal excretions reaching the effluent of wastewater, rivers, and lagoons, causing accumulation and generating resistance to certain pathogens, mainly zoonotic bacteria. The above has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…A very wide variety of antibiotic removal has been reported using different types of polymers and biopolymers [114,[211][212][213][214][215][216][217][218], among which we find removal of tetracyclines [112,113,219] and oxytetracyclines [114], ciprofloxacin [220], sulfamethoxazole [221], metronidazole [222], chloramphenicol [223], penicillin [224], amikacin [225], amoxicillin [59,125], among other antibiotics.…”
Section: Biopolymers For Amoxicillin Removalmentioning
confidence: 77%
“…A very wide variety of antibiotic removal has been reported using different types of polymers and biopolymers [114,[211][212][213][214][215][216][217][218], among which we find removal of tetracyclines [112,113,219] and oxytetracyclines [114], ciprofloxacin [220], sulfamethoxazole [221], metronidazole [222], chloramphenicol [223], penicillin [224], amikacin [225], amoxicillin [59,125], among other antibiotics.…”
Section: Biopolymers For Amoxicillin Removalmentioning
confidence: 77%
“…According to Patel et al [105], hydrogen bond formation between antibiotic molecules and carbonyl groups of banana peel biochar played a significant part in the adsorption process. Additionally, a previous study reported the elimination of antibiotics through dipole interactions [106]. For example, in a recent study by Liu et al [107], the authors highlighted that the oxygen-containing functional groups on the corn stover-based adsorbent surface, such as COOH, OH, and ether groups, could interact with carbonyl and hydroxyl groups of the naproxen via dipole-dipole interaction.…”
Section: Adsorption Mechanism For Antibiotics and Nsaidsmentioning
confidence: 99%
“…2) that confers rigidity. Fuoco (2012) [21] reported that tetracyclines inhibit protein synthesis in bacteria by the amino group at position C4 (antibacterial activity) and ketophenolic tautomers at positions C1 and C3 of ring A [22]. Fig.…”
Section: General Aspects Of Antibioticsmentioning
confidence: 99%
“…These interactions are the main mechanisms in retention processes, including i) electrostatic interactions, the main retention mechanism in most materials reported in the literature; ii) hydrophobic interactions; iii) hydrogen bonds; iv)𝜋-𝜋 interactions; and v) the morphology of the materials. In specific cases, the pore content [22,[128][129][130][131] would also be considered. Fig.…”
Section: Polymer Available Functional Group Referencementioning
confidence: 99%